Planning community participation in government emergency shelters after the aggression of 2014 on the Gaza Strip - Al- Tarshawi, Etimad A. (Journal of Risk and Crisis Management, 2019)
Community participation is a human right guaranteed in international covenants and national strategies، Thousands of thousands are displaced from their homes and many are housed in pre-built shelters.This paper aims at highlight the gap or harmonization of societal participation between the standards contained in international manuals and references and what is adopted and applied in the Gaza Strip. The researcher used the analytical descriptive approach through her review of international and national manuals and emergency plans and standards in the Gaza Strip. The recognition of community participation is very modest in the emergency literature of the Ministry of Social Development. The reports do not cover any practical or advanced stories in this field.The researcher attributed this gap to the lack of coherence in the level of planning between the international standards and national strategies on the one hand and the emergency plans prepared and implemented in government emergency shelters in the Gaza Strip.The researcher recommended the necessity of harmonizing the government shelters emergency plan with international standards and national strategies by re-reviewing them and explicitly including standards and procedures to activate community participation with the necessity of holding the necessary training with the basic skills of the emergency work teams.
Keywords: Community Participation; Crisis; Emergency Shelters; Sphere; Social Development Plan